PENINGKATAN KAPASITAS KADAR POSYANDU DALAM MENURUNKAN ANGKA STUNTING DI KOTA CIMAHI - Fahrurozi, Muhammad; Chairunnisa, Fatiha; Nuraeni, Fitri; Sulyaswati, Susi; Fadilla, Raihan Intan; Ramandha, Alya; Maryam, Fitri; Aulia, Rika; Damayanti, Iftitah Sekar; Sugianto, Diva; Afriyanti, Suci; Kahar, Kahar (Jurnal Pengabdian Masyarakat Kesehatan Indonesia, 2025)
Indonesia is among the countries with a high prevalence of stunting. National data indicate that efforts to reduce stunting require cross-sectoral attention, including at the primary service level such as Posyandu. The Indonesian Nutrition Status Survey (SSGI) reported that the stunting prevalence in Cimahi City is 16.4%, with a target to reduce the stunting rate to below 14% by 2024. Stunting is a major public health issue of national concern. This activity aims to enhance the capacity of Posyandu cadres in Cimahi City to support the national efforts in reducing stunting rates. The implementation method includes socialization activities, Self-Awareness Surveys (SMD), Community Consultations at the RW Level (MMRW), implementation, and evaluation. Information dissemination and training are delivered through effective media such as PowerPoint presentations, leaflets, X-banners, and videos. The results of the activity, assessed through pre-tests and post-tests, show an increase in the knowledge of Posyandu cadres, with the average score rising from 60/100 to 80/100, and some cadres even achieving the maximum score. This indicates that the provided materials were well received and understood. The conclusion of this empowerment activity is that there has been an increase in the knowledge capacity of Posyandu cadres regarding their roles and functions in stunting prevention.